Perbedaan arus puncak ekspirasi antara anak asma dengan obesitas dan anak asma tanpa obesitas - Nurul Hadi; Madarina Julia; Roni Naning (Jurnal Gizi Klinik Indonesia, 2013)
Background: Obesity in children is associated with impairment of pulmonary function and increased risk of asthma. Obesity in asthmatic children may reduce lung function, that can be assessed by peak flow meter, a practical and an inexpensive tool.Objectives: To compare the peak expiratory flow (PEF) between obese and non-obese asthmatic children.Method: We conducted a cross sectional study in Yogyakarta during March 2010-September 2012. Fifty obese asthmatic patients and 50 non obese asthmatic control subjects participated in this study. Inclusion criteria were asthmatic patient, according to Pedoman Nasional Asma Anak (PNAA), and 6-18 years of age. Exclusion criteria were asthmatic attack, respiratory disease, heart disease and congenital chest malformation. Obesity is defined as body mass index (BMI) for age more than +3 SD WHO growth chart standards BMI for age 2007 z-score. Z-score is calculated with WHO AnthroPlus for Personal Computers. Data PEF is taken with electrical peak flow meter when the patient was not suffering from asthma attack. Normal PEF was defined as PEF ≥80% average (predicted) value for height.Results: The mean of age of asthmatic children in this study was 9.38 years and 9.50 years for non obese and obese respectively. The PFR was not different between obese asthmatic children and non obese asthmatic children (p=0,83). Pearson correlation of PFR and z-score BMI for age was positive weak correlation (r=0.12). There was significant difference of PFR between z-score BMI for age <3,20 and z-score BMI for age ≥3.20 (p=0.03). Significant difference of PFR also appears in duration of illness (p<0.001).Conclusion: There is no PFR difference between obese asthmatic children and non-obese asthmatic children. The difference of PFR emerges when statistic analysis performed using z-score BMI ≥3.20.